Polymorphisms rs763110 in FASL is linked to hepatitis C virus infection among high-risk populations. Issue 3 (2nd July 2020) - Huang, P; Wang, CH; Zhuo, LY; Xia, XS; Yang, S; Zhang, JW; Fan, HZ; Wu, JJ; Yu, R; Yue, M; Zhang, Y
ABSTRACT: Background: The Fas cell surface death receptor (FAS) and Fas ligand (FASL) can participate in the apoptosis of immune cells and target cells infected with a virus through the FAS-FASL signalling pathway. The decoy receptor 3 (DCR3) can competitively inhibit the binding of FAS to FASL. Our aim is to investigate the effect of single nucleotide polymorphisms (SNPs) in FAS, FASL and DCR3 on hepatitis C virus (HCV) infection. Methods: Four SNPs (rs763110 in FASL, rs1324551 and rs2234767 in FAS and rs2257440 in DCR3 ) were genotyped in 1495 controls free of HCV, 522 individuals with spontaneous HCV clearance and 732 patients with hepatitis C virus infection. The RegulomeDB database and RNAfold web servers were used to explore potential biological functions of SNPs. Results: FASL rs763110 was associated with susceptibility to HCV infection, and not to CHC. The odds ratio (95% confidence interval) of HCV infection in high-risk populations carrying FASL rs763110-TT was 1.82 (1.36–2.51, P < 0.001) compared to that of CC genotypes and 1.93 (1.43–2.60, P < 0.001) higher than that of CC + CT genotypes. Based on computer simulation, FASL rs763110-T may affect the transcription of mRNA by affecting the binding of a transcription factor, leading to structural changes in mRNA. Conclusion: The genetic variant in FASL is linked with HCV infection, but not to spontaneous HCV clearance.